2001
DOI: 10.1007/s00277-001-0395-6
|View full text |Cite
|
Sign up to set email alerts
|

Vincristine as treatment for recurrent episodes of thrombotic thrombocytopenic purpura

Abstract: The clinical course of thrombotic thrombocytopenic purpura has dramatically improved after the introduction of plasma-based therapy, including plasma exchange and plasma infusion. However, a considerable number of patients still experience relapse after initial successful treatment. In this study, vincristine (VCR) was given as salvage treatment in 12 episodes of recurrent thrombotic thrombocytopenic purpura in seven patients, concomitantly with short-term plasma infusion. Complete remission (CR) was defined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 18 publications
0
23
0
3
Order By: Relevance
“…[3] Despite in vitro data in its support, it is not a first-line therapy, and plasma exchange remains the mainstay of treatment in TTP. [5] However, vincristine has been considered a part of a multimodal therapy in light of the TTP US Medical Research Group's results, where they have detailed a standardized regimen of plasma exchange, vincristine, and corticosteroids. [3] One study reviewed TTP cases over 15 years and found that 8 out of 29 patients (28%) achieved remission with plasma exchange alone, while 7 out of 8 patients (88%) achieved remission with plasma exchange and early vincristine.…”
mentioning
confidence: 99%
“…[3] Despite in vitro data in its support, it is not a first-line therapy, and plasma exchange remains the mainstay of treatment in TTP. [5] However, vincristine has been considered a part of a multimodal therapy in light of the TTP US Medical Research Group's results, where they have detailed a standardized regimen of plasma exchange, vincristine, and corticosteroids. [3] One study reviewed TTP cases over 15 years and found that 8 out of 29 patients (28%) achieved remission with plasma exchange alone, while 7 out of 8 patients (88%) achieved remission with plasma exchange and early vincristine.…”
mentioning
confidence: 99%
“…These patients require additional treatment methods including rituximab and immunosuppressive agents such as high-dose methylprednisolone, VCR, cyclophosphamide, cyclosporine, or splenectomy [16]. Administration of VCR can be used as an additional therapy with TPE for patients who do not respond to initial plasma exchange therapy [17], or it can be used for relapsed patients [18]. Our patient did not respond to initial TPE, so VCR was used in addition to plasma exchange.…”
Section: Discussionmentioning
confidence: 88%
“…Although platelet transfusion may be beneficial in clinically serious bleeding, it is not routinely recommended (18–21). Cases that are resistant to usual therapy are treated with immunomodulation (22) with vincristine (23, 24) cyclophosphamide (25), cyclosporine or splenectomy (26). …”
Section: Discussionmentioning
confidence: 99%